Sulfur amino acids in methionine-restricted rats: hyperhomocysteinemia. - Elshorbagy, A; Valdivia-Garcia, M; Refsum, H; Smith, A; Mattocks, D; Perrone, C (2010)
OBJECTIVE: Dietary methionine restriction in Fischer-344 rats favorably influences visceral fat mass, insulin sensitivity, metabolic parameters, and longevity. However, little is known about the effects of methionine restriction on serum methionine and its downstream sulfur amino acids. We investigated the serum sulfur amino acid profile of male Fischer-344 rats fed a methionine-restricted diet for 3 mo. METHODS AND RESULTS: Using tandem mass spectrometry, we observed marked reduction in serum concentrations of methionine, cystathionine, cysteine, and taurine in methionine-restricted rats compared with control (P<0.001) and a 2.5-fold elevation of homocysteine (P<0.001). CONCLUSION: This suggests that homocysteine trans-sulfuration may be inhibited by methionine restriction, and that some of the effects of methionine restriction may be mediated by changes in sulfur amino acids downstream of methionine.